A family is a family is a family - O'Leary, Sara (Groundwood Books : House of Anansi Press, 2016)
"When a teacher asks the children in her class to think about what makes their families special, the answers are all different in many ways -- but the same in the one way that matters most of all. One child is worried that her family is just too different to explain, but listens as her classmates talk about what makes their families special. One is raised by a grandmother, and another has two dads. One is full of stepsiblings, and another has a new baby"--Publisher.